A green synthesis method of cyanuric acid

CN122187753BActive Publication Date: 2026-10-09SHANDONG WO LAN BIOLOGICAL GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610305512.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-13
Publication Date
2026-10-09
Estimated Expiration
2046-03-13

AI Technical Summary

Technical Problem

然而,离子液体体系仍面临难以逾越的产业化瓶颈

Benefits of technology

(1)本发明所提出的氰尿酸绿色合成方法,通过引入自主设计的锆基金属有机框架-蒙脱土异质结构无机改性材料作为核心催化剂,产生了显著且多方面的积极技术效果。首先,该方法最直接的效果体现在反应效率与选择性的显著提升上。相较于传统尿素热解法所需的高温苛刻条件,本发明成功将反应温度降低,反应时间缩短。在这一优化条件下,由于该异质结构材料同时提供了高密度且均匀分布的路易斯酸活性位点以及独特的纳米限域空间,尿素分子的活化及后续异氰酸中间体的三聚反应得以高效、定向进行。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a cyanuric acid green synthesis method in the field of green chemistry and chemical technology; the method uses self-made zirconium metal organic framework montmorillonite heterostructure inorganic modified material as a catalyst, is mixed with urea, and then is subjected to a solvent-free solid phase condensation reaction in an inert atmosphere. After the reaction product is washed with hot water, is separated through filtration, and the filtrate is cooled and crystallized, cyanuric acid product is obtained, and the catalyst can be recycled after being recovered and regenerated. The zirconium metal organic framework montmorillonite heterostructure inorganic modified material is made through the following steps: modifying montmorillonite by silylating an amine group, coordinating a zirconium precursor, hydrothermally synthesizing a heterostructure, and stepwise heat treatment. The application has the advantages of simple process, significantly lower reaction temperature than traditional pyrolysis, efficient and recyclable catalyst, and realization of low-energy-consumption and environment-friendly synthesis of cyanuric acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of green chemistry and chemical engineering technology, and specifically relates to a green synthesis method for cyanuric acid. Background Technology

[0002] As a key chemical intermediate, the green innovation of its production technology has always been an important issue for the industry. This compound is a core raw material for manufacturing highly efficient disinfectants such as chloroisocyanurates, flame retardants for polymer materials, and various fine chemicals, and market demand continues to grow. However, its mainstream industrial production has long relied on the traditional solid-phase method of high-temperature pyrolysis of urea. This process usually requires high-temperature conditions, which not only consumes a lot of energy but also has many inherent defects. The high-temperature environment easily leads to local overheating and coking of the reactants, resulting in reduced product purity and darker color, requiring complex subsequent refining processes. At the same time, the decomposition and condensation pathways of urea at high temperatures are difficult to control precisely, increasing side reactions and resulting in unsatisfactory selectivity of the target product. A more prominent problem is that a large amount of ammonia is continuously released during the reaction, which will cause environmental pollution if not properly recovered and treated, and also places extremely high demands on the sealing and corrosion resistance of the production equipment. Another previously used sulfuric acid process, while lowering the reaction temperature, uses highly corrosive concentrated sulfuric acid as a solvent, generating large amounts of acidic wastewater during post-processing. This leads to severe equipment corrosion and significant challenges in waste treatment, resulting in substantial shortcomings in both economics and environmental impact, and it has been gradually phased out. Therefore, developing a new synthesis process that can operate under mild conditions, avoids the use of harmful solvents, and is highly efficient and energy-saving is of urgent practical significance for improving the industry's technological level and achieving green manufacturing goals.

[0003] To overcome the drawbacks of traditional methods, academia and industry have explored various improvement paths, among which the research on ionic liquid catalytic systems has made some progress. Some researchers have used ionic liquids with specific structures, such as imidazoles, as reaction media and catalysts, successfully reducing the urea condensation temperature to around 200 degrees Celsius and increasing the reaction rate by utilizing their low volatility, high thermal stability, and designable acid-base properties. This type of method has initially demonstrated the feasibility of controlling the reaction pathway through catalysis, providing a new approach to reducing energy consumption. However, ionic liquid systems still face insurmountable industrialization bottlenecks. First, ionic liquids themselves are expensive, making large-scale use economically unfeasible. Second, as homogeneous catalysts, the separation and recovery of ionic liquids from products is difficult, usually requiring complex distillation or extraction steps. Furthermore, during recycling, catalytic efficiency is easily reduced due to decomposition, impurity accumulation, or functional group deactivation, resulting in insufficient stability. Furthermore, related research has largely focused on exploring derivative fields such as the use of cyanuric acid as a precursor for the synthesis of novel carbon and nitrogen materials, while neglecting fundamental innovations in its bulk synthesis processes, particularly the systematic design of heterogeneous, easily separable, and long-term cyclic solid catalytic materials. Current technologies have yet to provide a comprehensive solution that combines high catalytic activity, high selectivity, excellent cycling stability, and low-cost potential.

[0004] In view of this, the present invention aims to propose a novel green synthesis paradigm for cyanuric acid, the core of which lies in abandoning the dependence on complex solvent systems and instead designing and creating a multifunctional solid inorganic modifier with independent intellectual property rights. This material is designed with a unique composite heterogeneous structure, achieving efficient and targeted catalysis of urea molecule decomposition and isocyanate trimerization under mild thermal conditions through carefully constructed active sites and a nano-confined environment. The process route of this invention is greatly simplified; it only requires simple mixing of urea and the modified material, heating in an inert atmosphere, and obtaining a high-purity product through physical separation and water washing after the reaction. The catalyst can be reused repeatedly after simple regeneration. This method fundamentally avoids the use of solvents and their subsequent recycling processes, eliminating wastewater generation and corrosion risks at the source; the significant reduction in reaction temperature directly leads to energy savings; and the easy separation characteristics and recycling potential of the solid catalyst greatly improve the economics of the process. This invention not only provides a practical green technology path for cyanuric acid production but also provides new materials and methods for similar condensation reactions. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a green synthesis method for cyanuric acid.

[0006] A first aspect of the present invention provides a green synthesis method for cyanuric acid, comprising the following steps: S1. In a mortar, urea and zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material are ground and mixed to obtain a mixture. The mixture is then transferred to a covered quartz boat to obtain a quartz boat containing the material. S2. Place the quartz boat containing the material into the muffle furnace, introduce argon gas, and heat to 180-220℃ to react; S3. After the reaction is complete, allow it to cool naturally to 60-80℃ and remove the reaction product. Transfer the reaction product to a beaker, add deionized water at 78-82℃, and stir. Then filter under reduced pressure to obtain a wet filter cake and filtrate. Wash the wet filter cake with deionized water at 78-82℃ to obtain a washed wet filter cake, filtrate, and washing liquid. S4. The washed wet filter cake is redispersed in hot water at 78-82℃, centrifuged at high speed, and the solid precipitate is collected. The solid precipitate is dried at 78-82℃, and then calcined at 298-302℃ in an argon atmosphere to obtain the regenerated zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material. The filtrate and washing liquid obtained in step S3 are cooled to 0-5℃, allowed to stand, filtered again to obtain crystals. The crystals are washed with deionized water and finally dried in a vacuum drying oven at 78-82℃.

[0007] In this invention, the green synthesis mechanism of cyanuric acid fully demonstrates the efficient reshaping and optimization of traditional thermal conversion pathways by the "nanoreactor" in heterogeneous catalysis. When urea molecules are mixed with the catalyst and heated, the reaction process is completely different from the random thermal polycondensation without a catalyst. First, the high-density zirconium Lewis acid sites on the catalyst surface and within the nanopores have a strong electrophilic adsorption capacity for the carbonyl oxygen of urea molecules. This adsorption significantly polarizes and weakens the carbon-nitrogen bonds in urea molecules, thereby greatly reducing the activation energy barrier for the first step of urea decomposition to generate isocyanate monomers, thus lowering the start-up temperature of the entire condensation reaction. Subsequently, the generated isocyanate monomers are rapidly confined within the uniformly composed and appropriately sized nanopores of the catalyst's metal-organic framework. This nanoconfinement effect plays several key roles: First, it confines the reaction intermediates within a local space, significantly increasing their effective concentration and accelerating the trimerization rate. Second, the specific geometry and size of the pores spatially constrain and guide the orientation of isocyanate molecules, working in conjunction with the acidic sites on the pore walls to precisely guide the three isocyanate molecules to cyclize in the most favorable orientation. This results in near-specific selectivity for the formation of the target product, cyanuric acid, effectively inhibiting the formation of linear polymers or other byproducts. Throughout the catalytic cycle, the adsorption strength of the cyanuric acid product at the active sites is moderate at the reaction temperature, allowing for timely desorption and removal from the pores, thus regenerating the active centers and enabling continuous catalysis. After the reaction, the product can be separated from the solid catalyst through simple thermal filtration. Furthermore, after moderate calcination under an inert atmosphere to remove trace amounts of surface-adsorbed organic matter, the active centers and nanopore structure of the catalyst can be fully restored, achieving cyclic regeneration of catalytic performance. This mechanism transforms the original high-temperature, high-energy-consumption, and poorly selective direct pyrolysis process of urea into a highly efficient and green process that is precisely catalyzed by specific solid materials under mild conditions. Its essence is to achieve intelligent control of the reaction path at the molecular level through material innovation.

[0008] As a preferred technical solution of the present invention, in step S1, the mass ratio of the urea and the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material is (4.8-5.2):(0.4-0.6).

[0009] As a preferred embodiment of the present invention, in step S2, the reaction time is 3-5 hours after heating to 180-220°C.

[0010] As a preferred embodiment of the present invention, in step S3, the stirring time is 20-40 minutes.

[0011] As a preferred embodiment of the present invention, in step S4, the subsequent calcination at 298-302°C in an argon atmosphere takes 2-4 hours.

[0012] As a preferred embodiment of the present invention, the preparation steps of the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material include: A1. By weight, place 8-12 parts of sodium-based montmorillonite in a three-necked flask, add 280-320 parts of deionized water, and stir at 78-82℃ to obtain a suspension; add 35-37 parts of a mixed solution of ethanol and water of 3-aminopropyltriethoxysilane dropwise to the suspension to adjust the pH to 4-5; reflux the reaction at 84-86℃ under nitrogen protection; after the reaction is complete, collect the solid by centrifugation, wash the solid alternately with ethanol and deionized water, and dry it in a vacuum drying oven at 78-82℃ to obtain silanized amino-modified montmorillonite; A2. Disperse silanized amine-modified montmorillonite in 180-200 parts of N,N-dimethylformamide and sonicate to obtain a suspension. Under stirring, dissolve 3.5-4.5 parts of zirconium tetrachloride in 45-50 parts of anhydrous N,N-dimethylformamide and then add it dropwise to the suspension to obtain a mixture. Transfer the mixture to an ice-water bath and continue stirring at 0-5℃. Centrifuge and wash with N,N-dimethylformamide to obtain a zirconium-amine coordination intermediate. A3. Dissolve 1.6-2.0 parts of 2-aminoterephthalic acid in 140-150 parts of N,N-dimethylformamide to obtain solution A; dissolve 2.8-3.2 parts of benzoic acid in 45-48 parts of N,N-dimethylformamide to obtain solution B; redisperse the zirconium-amine coordination intermediate in 92-96 parts of N,N-dimethylformamide to obtain a zirconium-amine coordination intermediate suspension; add the zirconium-amine coordination intermediate suspension to a high-pressure hydrothermal reactor; add solution A to the high-pressure hydrothermal reactor, then add solution B; place the high-pressure hydrothermal reactor in a 115-125℃ forced-air drying oven to react and obtain the reaction product; A4. Cool the reaction product to room temperature, centrifuge to collect the precipitate, wash the precipitate sequentially with N,N-dimethylformamide and anhydrous methanol to obtain the washed precipitate, soak the washed precipitate in methanol to obtain the wet material; dry the wet material at 78-82℃ to obtain the powder, place the powder in a tube furnace and perform heat treatment under argon protection.

[0013] In this invention, the preparation reaction mechanism of the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material embodies a precisely controlled process from molecular design to macroscopic structural construction. The core lies in constructing a stable and synergistic heterostructure interface through multi-step chemical interactions. This process begins with the basic modification of natural layered silicate montmorillonite. Hydrolysis and condensation reactions using silane coupling agents under mild acid catalysis are employed to covalently graft organic amine functional groups with strong coordination capabilities onto the montmorillonite. This step not only expands the interlayer distance of montmorillonite but, more importantly, introduces a large number of uniformly distributed nitrogen active sites on its surface and between layers, laying the chemical foundation for subsequent metal center anchoring. Subsequently, in a strictly controlled anhydrous and low-temperature environment, a highly active zirconium metal salt precursor is introduced into the system. Its metal ions rapidly coordinate with the newly introduced amine nitrogen atoms on the montmorillonite surface and the hydroxyl oxygen atoms of the silicate framework itself, forming an atomically dispersed zirconium species coordination layer. This coordination intermediate is a crucial turning point in the entire material synthesis. It is not a simple physical adsorption process, but rather establishes a robust chemical bridge between montmorillonite and the metal-organic framework (MOF) to be grown. The subsequent hydrothermal reaction is the decisive stage for the nucleation and growth of the heterostructure. Driven by high temperature and pressure, the added organic linker molecules and pre-coordinated zirconium species undergo directional assembly on the surface of the montmorillonite sheets and within the extended interlayer space. Due to the guiding effect and spatial confinement effect of the amine groups on the montmorillonite surface, the crystal growth of the MOF is preferentially guided to heterogeneous epitaxy on the montmorillonite substrate, rather than homogeneous self-nucleation, thus forming a heterostructure in which MOF nanocrystals and montmorillonite sheets are tightly bonded by chemical bonds. The final step-by-step heat treatment serves the dual purpose of annealing and activation. While removing residual solvent molecules and unstable coordinated organic matter from the pores, it further strengthens the chemical bonding at the heterostructure interface and optimizes the crystallinity and porosity of the MOF components, ultimately exposing abundant and stable bifunctional catalytic active centers composed of zirconium-oxygen clusters and acidic sites in montmorillonite.

[0014] As a preferred embodiment of the present invention, in step A1, the reflux reaction at 84-86°C is carried out for 24-30 hours.

[0015] As a preferred embodiment of the present invention, in step A2, the stirring time at 0-5°C is 6-8 hours.

[0016] As a preferred embodiment of the present invention, in step A3, the reaction time in the 115-125℃ forced-air drying oven is 72-80h.

[0017] As a preferred embodiment of the present invention, in step A4, the heat treatment step involves raising the temperature to 245-255°C and holding it thereafter; then raising the temperature further to 295-305°C and holding it thereafter.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The green synthesis method for cyanuric acid proposed in this invention, by introducing a self-designed zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material as the core catalyst, has produced significant and multifaceted positive technical effects. First, the most direct effect of this method is reflected in the significant improvement of reaction efficiency and selectivity. Compared with the harsh high-temperature conditions required by the traditional urea pyrolysis method, this invention successfully reduces the reaction temperature and shortens the reaction time. Under these optimized conditions, because the heterostructure material simultaneously provides high-density and uniformly distributed Lewis acid active sites and a unique nano-confined space, the activation of urea molecules and the subsequent trimerization reaction of isocyanate intermediates can proceed efficiently and directionally.

[0019] (2) The technical advantages of this invention are prominently reflected in the greening, simplification, and high economic efficiency of its entire process. The entire synthesis reaction is completed in a solid-phase system without any liquid solvent, completely avoiding the use of highly corrosive solvents in traditional processes such as the sulfuric acid process. The requirements for reactor materials are significantly reduced, and the generation of hazardous wastes such as acidic wastewater is eliminated at the source, resulting in significant environmental benefits. After the reaction is completed, the separation process between the product and the solid catalyst is extremely simple. High-purity cyanuric acid crystals can be obtained simply through physical operations such as hot water washing, filtration, and cooling crystallization. The process route is short and the operation is highly safe. Particularly important is that after the catalyst is activated by calcination in a mild inert atmosphere, its catalytic active center and heterostructure are completely restored and it can be reused. This greatly reduces the material cost and gives the entire process excellent circular economy characteristics, laying a solid cost foundation for its industrial application.

[0020] (3) The deeper technical effect of this invention stems from the synergistic catalytic mechanism brought about by the forward-looking structure of the designed catalyst itself. The zirconium-based metal-organic framework and montmorillonite are not simply composites, but form a stable heterogeneous interface through chemical bonding. The two-dimensional layered structure of montmorillonite serves as a supporting framework, effectively preventing the aggregation of metal-organic framework nanoparticles and exposing more edge active sites; while the highly ordered microporous structure of the metal-organic framework acts like a precise "molecular reactor," guiding the isocyanate, a product of urea decomposition, to undergo orderly trimerization within its pores through size confinement effects, thereby achieving unprecedented precise control over the cyanuric acid synthesis reaction. This fundamental enhancement and optimization of classic chemical reactions through material innovation not only provides a new technical solution for the green manufacturing of cyanuric acid, but also provides a reference material design idea and process development paradigm for other similar solid-phase condensation reactions. Detailed Implementation

[0021] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention. Example

[0022] This embodiment provides a green synthesis method for cyanuric acid, including the following steps: The preparation steps of zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified materials are as follows: A1. Accurately weigh 10.00 g of sodium montmorillonite and place it in a 500 mL three-necked flask. Add 300 g of deionized water to the flask. Place the flask on a thermostatic magnetic stirrer, install the reflux condenser and nitrogen inlet tube, turn on the stirrer, and set the temperature to 80.0 °C. Once the suspension temperature stabilizes at 80.0 °C, slowly add the prepared modified solution (composed of 3.00 g of 3-aminopropyltriethoxysilane, 19.00 g of anhydrous ethanol, and 15.00 g of water) dropwise through a constant-pressure dropping funnel, controlling the addition time within 30 min. After the addition is complete, use a micropipette to add glacial acetic acid to precisely adjust the pH of the reaction system to 4.5. Subsequently, continuously purge the system with high-purity nitrogen (flow rate 50 mL / min) to remove air, and carry out the reflux reaction at 85.0 °C for a strictly controlled reaction time of 26 h.

[0023] After the reaction was complete, the heating was turned off, and the reaction mixture was transferred to a 250 mL polypropylene centrifuge tube. The tube was centrifuged at 8000 rpm for 10 min using a high-speed centrifuge, and the supernatant was carefully discarded. The solid precipitate was washed alternately with 50 mL of anhydrous ethanol and 50 mL of deionized water, centrifuged at 8000 rpm for 5 min after each wash, and this washing process was repeated three times. The final solid was transferred to a petri dish and placed in a vacuum drying oven at 80.0 °C for 12 h to obtain silanized amino-modified montmorillonite, denoted as MMT-NH2, which was then stored in a desiccator for later use.

[0024] A2. Transfer all the prepared MMT-NH2 to a 500mL single-necked flask and add 190g of N,N-dimethylformamide. Place the flask in an ultrasonic cleaner and sonicate at 40kHz for 30min to fully disperse the MMT-NH2 and obtain a homogeneous suspension. In another 100mL beaker, accurately weigh 4.00g of zirconium tetrachloride and add 48g of anhydrous N,N-dimethylformamide. Dissolve the zirconium tetrachloride completely under magnetic stirring to obtain a clear solution.

[0025] Under mechanical stirring (500 rpm), zirconium tetrachloride solution was slowly added dropwise to the MMT-NH2 suspension using a constant-pressure dropping funnel over approximately 20 minutes. After the addition was complete, the entire flask was transferred to an ice bath containing an ice-water mixture to maintain the reaction temperature at 2.0 ± 0.5 °C. The reaction was continued at this low temperature with stirring for 7.0 h.

[0026] After the reaction was complete, the mixture was transferred to a centrifuge tube and centrifuged at 8000 rpm for 10 min at 2.0 °C. The supernatant was discarded. The solid precipitate was washed three times with fresh N,N-dimethylformamide (30 mL each time), and centrifuged after each wash. The obtained solid is the zirconium-amine coordination intermediate, denoted as Zr-MMT, which can be temporarily stored in N,N-dimethylformamide for later use.

[0027] A3. Prepare two solutions: Solution A: Weigh 1.80g of 2-aminoterephthalic acid and dissolve it in 142g of N,N-dimethylformamide, using sonication to aid dissolution; Solution B: Weigh 3.00g of benzoic acid and dissolve it in 48g of N,N-dimethylformamide.

[0028] All the Zr-MMT intermediates obtained in step A2 were redispersed in 95g of N,N-dimethylformamide to obtain a suspension. This suspension was then transferred to a 500mL high-pressure hydrothermal reactor lined with polytetrafluoroethylene. Subsequently, solutions A and B were added sequentially to the reactor liner. The liner and outer vessel were tightly sealed, and the reactor was placed in a forced-air drying oven. The reaction temperature was set to 120.0℃, and the reaction time was 75h.

[0029] After the reaction was complete, the mixture was allowed to cool naturally to room temperature. The reaction vessel was opened, and all the reaction product was transferred to centrifuge tubes. The precipitate was collected by centrifugation at 8000 rpm for 10 min. The precipitate was washed sequentially with N,N-dimethylformamide (50 mL × 3 times) and anhydrous methanol (50 mL × 3 times). The washed solid was then immersed in 200 mL of methanol and allowed to stand at room temperature. Fresh methanol was replaced every 24 h for a total of 3 times to perform solvent exchange. Finally, the solid was removed and dried overnight (approximately 12 h) in a vacuum drying oven at 80.0 °C to obtain a light yellow powder precursor.

[0030] A4. Spread the dried powder precursor evenly in a quartz boat, and then place the quartz boat in the isothermal zone of a tube furnace. Seal the tube furnace and purge with high-purity argon gas at a flow rate of 50 mL / min for 30 min, then purge the air. Under continuous argon gas purging, perform programmed temperature rise heat treatment: first, raise the temperature from room temperature to 250.0 °C at a rate of 2.0 °C / min and hold at 250.0 °C for 120 min; then, continue raising the temperature to 300.0 °C at a rate of 1.0 °C / min and hold at 300.0 °C for 60 min. After heat treatment, stop heating and allow to cool naturally to room temperature in an argon gas flow. Collect the obtained target modified material, name it Zr-MOF-MMT, and store it in a desiccator.

[0031] The preparation steps of the green synthesis method for cyanuric acid are as follows: S1. In an agate mortar, accurately weigh 5.00 g of urea and 0.50 g of the Zr-MOF-MMT modified material prepared above using an analytical balance. Grind and mix manually for 10 min until the mixture is visually uniform and there are no visible particle agglomerations. Transfer the uniformly mixed material to a 50 mL covered quartz boat and gently compact and level it with a spatula.

[0032] S2. Place the quartz boat containing the material into the center of the muffle furnace. Connect the muffle furnace inlet and outlet to the inert gas pipeline, and introduce high-purity argon gas at a flow rate of 80 mL / min for 10 minutes to displace the air in the furnace. Then, set the muffle furnace temperature program: increase from room temperature to 200.0℃ at a rate of 5.0℃ / min, start timing after reaching 200.0℃, and maintain the temperature for 4.0 hours. Keep the argon gas flowing throughout the entire heating and reaction process.

[0033] S3. After the reaction time is reached, turn off the muffle furnace heating power, continue the argon gas flow, and allow the furnace to cool naturally to 70.0℃. Open the furnace door and remove the quartz boat. Transfer all the solid product that has agglomerated after the reaction in the quartz boat to a 250mL beaker. Add 150mL of deionized water preheated to 80.0℃ to the beaker. Place the beaker on a magnetic stirrer and stir continuously at 500rpm for 30min.

[0034] Pour the mixture from the beaker into a Buchner funnel pre-lined with slow-moving quantitative filter paper, and turn on the vacuum pump for reduced-pressure filtration. After filtration, rinse the beaker and filter paper twice (15 mL each time) with 30 mL of deionized water at 80.0 °C to ensure thorough washing. Collect all filtrate and washings, labeling it Mother Solution A. Retain the resulting wet filter cake.

[0035] S4. Transfer the wet filter cake to a 100 mL centrifuge tube, add 80 mL of hot water at 80.0 °C, stir with a glass rod, and then centrifuge at 8000 rpm for 10 min. Discard the supernatant and collect the solid precipitate at the bottom. Transfer this solid precipitate to a petri dish and dry it in an oven at 80.0 °C for 6 h. Load the dried solid powder into a porcelain boat, place it in a tube furnace, and calcine it at 300.0 °C for 180 min under an argon atmosphere (flow rate 50 mL / min). After calcination, cool to room temperature to obtain the regenerated Zr-MOF-MMT catalyst, weigh it, and record the recovery rate.

[0036] The mother liquor A collected in step S3 was transferred to a 250 mL Erlenmeyer flask. The flask was placed in an ice-water bath and slowly cooled to 2.0 °C. It was then allowed to stand at 2.0 °C for 120 min to allow cyanuric acid crystals to fully separate. The mixture was then filtered again under reduced pressure. The resulting white crystals were washed twice with 20 mL of deionized water pre-cooled to 2.0 °C. Finally, the crystals were dried in a vacuum drying oven at 80.0 °C for 6 h to obtain the final cyanuric acid product. Example

[0037] The difference between this embodiment and Embodiment 1 is that the preparation steps of the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material are as follows: A1. Accurately weigh 9.00 g of sodium-based montmorillonite and place it in a 500 mL three-necked flask. Add 290 g of deionized water. Turn on the stirrer and heat to 79.0 °C. Slowly add the modification solution (2.80 g of 3-aminopropyltriethoxysilane dissolved in 19.00 g of anhydrous ethanol and 13.20 g of water) dropwise to the suspension over 25 min. Adjust the pH to 4.2 with glacial acetic acid. Reflux the reaction at 84.0 °C for 28.0 h under nitrogen protection (flow rate 50 mL / min). After the reaction, centrifuge and wash the solid three times alternately with ethanol and deionized water, each time at 8000 rpm for 5 min. Dry the solid in a vacuum drying oven at 80.0 °C for 12 h to obtain silanized amino-modified montmorillonite.

[0038] A2. All modified montmorillonite was dispersed in 180g of N,N-dimethylformamide and sonicated for 30min. While stirring (500rpm), 45g of anhydrous N,N-dimethylformamide solution containing 3.80g of zirconium tetrachloride was added dropwise to the suspension. The mixture was transferred to an ice bath, and the temperature was controlled at 1.0±0.5℃. The reaction was stirred for 6.5h. After the reaction, the mixture was centrifuged at 8000rpm for 10min at 1.0℃. The solid was collected and washed three times with N,N-dimethylformamide to obtain the zirconium-amine coordination intermediate.

[0039] A3. Prepare solution A (1.70 g 2-aminoterephthalic acid dissolved in 140 g N,N-dimethylformamide) and solution B (2.90 g benzoic acid dissolved in 45 g N,N-dimethylformamide). Redisperse all the zirconium-amine coordination intermediate in 92 g L N,N-dimethylformamide and transfer to the liner of a 500 mL high-pressure hydrothermal reactor. Add solutions A and B sequentially. Seal the reactor and place it in a forced-air drying oven, reacting at 118.0 °C for 78.0 h. After cooling, centrifuge to collect the precipitate, washing it three times each with N,N-dimethylformamide and anhydrous methanol. Then, immerse the solid in methanol for solvent exchange for 72 h (changing the solvent every 24 h). Finally, dry overnight at 80.0 °C to obtain the powdered precursor.

[0040] A4. The powder precursor was placed in a quartz boat in a tubular furnace and heat-treated under an argon flow (50 mL / min): the temperature was increased to 248.0℃ at 2.0℃ / min and held for 120 min; then the temperature was increased to 298.0℃ at 1.0℃ / min and held for 60 min. After cooling, the modified material was obtained.

[0041] The preparation steps of the green synthesis method for cyanuric acid are as follows: S1. Weigh 5.10g of urea and 0.45g of the above modified material into a mortar and grind them together for 10 minutes until homogeneous. Transfer the entire mixture to a 50mL capped quartz boat and spread it evenly.

[0042] S2. Place the quartz boat into the muffle furnace, pass argon gas at a flow rate of 80 mL / min for 10 min, then raise the temperature to 185.0℃ at a rate of 5.0℃ / min and react at a constant temperature for 5.0 h, maintaining an argon gas flow throughout the process.

[0043] S3. After the reaction is complete and the mixture is cooled to 65.0℃, the product is removed. The product is transferred to a 250mL beaker, and 155mL of deionized water at 79.0℃ is added. The mixture is stirred at 500rpm for 25min. Then, the mixture is filtered under reduced pressure, and the filter cake is washed twice with 30mL (79.0℃) of deionized water. All filtrates and washings are collected.

[0044] S4. The wet filter cake was redispersed in 80 mL of hot water at 79.0 °C, and the solid was collected by centrifugation at 8000 rpm for 10 min. The solid was dried at 80.0 °C for 6 h, and then placed in a tube furnace and calcined at 299.0 °C for 150 min under argon atmosphere to regenerate the catalyst. The combined filtrates were cooled to 1.0 °C and allowed to stand for 120 min to crystallize. The crystals were filtered, washed with 20 mL of cold deionized water, and finally dried under vacuum at 80.0 °C for 6 h to obtain the cyanuric acid product. Example

[0045] The difference between this embodiment and Embodiment 1 is that the preparation steps of the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material are as follows: A1. Accurately weigh 11.00 g of sodium-based montmorillonite and place it in a 500 mL three-necked flask. Add 310 g of deionized water. Turn on the stirrer and heat to 81.0 °C. Slowly add the modification solution (3.20 g of 3-aminopropyltriethoxysilane dissolved in 18.00 g of anhydrous ethanol and 15.00 g of water) dropwise to the suspension over 35 min. Adjust the pH to 4.8 with glacial acetic acid. Reflux the reaction at 86.0 °C for 25.0 h under nitrogen protection (flow rate 50 mL / min). After the reaction, centrifuge and wash the solid three times alternately with ethanol and deionized water, each time at 8000 rpm for 5 min. Dry the solid in a vacuum drying oven at 80.0 °C for 12 h to obtain silanized amino-modified montmorillonite.

[0046] A2. Disperse all modified montmorillonite in 200g N,N-dimethylformamide and sonicate for 30min. While stirring (500rpm), add dropwise a solution of 50g anhydrous N,N-dimethylformamide containing 4.20g zirconium tetrachloride to the suspension. Transfer the mixture to an ice bath, maintain the temperature at 4.0±0.5℃, and stir for 7.5h. After the reaction, centrifuge at 8000rpm for 10min at 4.0℃, collect the solid, and wash three times with N,N-dimethylformamide to obtain the zirconium-amine coordination intermediate.

[0047] A3. Prepare solution A (1.90 g 2-aminoterephthalic acid dissolved in 150 g mL N,N-dimethylformamide) and solution B (3.10 g benzoic acid dissolved in 48 g N,N-dimethylformamide). Redisperse all the zirconium-amine coordination intermediate in 96 g N,N-dimethylformamide and transfer it to the liner of a 500 mL high-pressure hydrothermal reactor. Add solutions A and B sequentially. Seal the reactor and place it in a forced-air drying oven, reacting at 122.0 °C for 72.0 h. After cooling, collect the precipitate by centrifugation, washing it three times each with N,N-dimethylformamide and anhydrous methanol. Then, immerse the solid in methanol for solvent exchange for 72 h (changing the solvent every 24 h). Finally, dry overnight at 80.0 °C to obtain the powdered precursor.

[0048] A4. The powder precursor was placed in a quartz boat in a tubular furnace and heat-treated under an argon flow (50 mL / min): the temperature was increased to 252.0℃ at 2.0℃ / min and held for 120 min; then the temperature was increased to 302.0℃ at 1.0℃ / min and held for 60 min. After cooling, the modified material was obtained.

[0049] The preparation steps of the green synthesis method for cyanuric acid are as follows: S1. Weigh 4.90g of urea and 0.55g of the above modified material into a mortar and grind them together for 10 minutes until homogeneous. Transfer the entire mixture to a 50mL capped quartz boat and spread it evenly.

[0050] S2. Place the quartz boat into the muffle furnace, pass argon gas at a flow rate of 80 mL / min for 10 min, then raise the temperature to 215.0℃ at a rate of 5.0℃ / min and react at a constant temperature for 3.5 h, maintaining an argon gas flow throughout the process.

[0051] S3. After the reaction is complete and the mixture is cooled to 75.0℃, the product is removed. The product is transferred to a 250mL beaker, and 145mL of deionized water at 81.0℃ is added. The mixture is stirred at 500rpm for 35min. Then, the mixture is filtered under reduced pressure, and the filter cake is washed twice with 30mL (81.0℃) of deionized water. All filtrates and washings are collected.

[0052] S4. The wet filter cake was redispersed in 80 mL of hot water at 81.0 °C, and the solid was collected by centrifugation at 8000 rpm for 10 min. The solid was dried at 80.0 °C for 6 h, and then placed in a tube furnace and calcined at 301.0 °C for 210 min under argon atmosphere to regenerate the catalyst. The combined filtrates were cooled to 4.0 °C and allowed to stand for 120 min to crystallize. The crystals were filtered, washed with 20 mL of cold deionized water, and finally dried under vacuum at 80.0 °C for 6 h to obtain the cyanuric acid product.

[0053] Comparative Example 1 The difference between this comparative example and Example 1 is that no catalyst is used in this comparative example. The preparation steps of the cyanuric acid synthesis method are as follows: Weigh 5.00 g of urea and place it directly into a 50 mL covered quartz boat and spread it evenly. Place the quartz boat in a muffle furnace, introduce argon gas (80 mL / min), and heat to 200.0 °C at 5.0 °C / min, and react at this temperature for 4.0 h. After the reaction is completed, cool to 70.0 °C and remove the product. The product is a hard, dark yellow agglomerate. Grind it into powder, add 150 mL of 80.0 °C deionized water, stir for 30 min, filter, cool the filtrate to 2.0 °C to crystallize, and dry to obtain a solid.

[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that this comparative example uses unmodified sodium montmorillonite. The preparation steps of the cyanuric acid synthesis method are as follows: Weigh 5.00 g of urea and 0.50 g of unmodified sodium montmorillonite, and grind and mix for 10 min. The conditions and operations of all subsequent reaction, separation, and purification steps are exactly the same as in Example 1. Crystals are finally obtained.

[0055] Comparative Example 3 The difference between this comparative example and Example 1 is that the silanization and amine modification step is omitted in the preparation of the material in this comparative example. The material preparation steps are as follows: 10.00g of raw sodium-based montmorillonite was directly subjected to steps A2 (reaction with 4.00g of zirconium tetrachloride at 2.0℃), A3 (hydrothermal reaction with 1.80g of 2-aminoterephthalic acid and 3.00g of benzoic acid at 120.0℃), and A4 (heat treatment) of Example 1 to obtain the comparative material. The cyanuric acid synthesis steps are as follows: 5.00g of urea and 0.50g of the comparative material were weighed, and all subsequent synthesis and separation steps were exactly the same as in Example 1. Finally, the cyanuric acid product was obtained.

[0056] In accordance with national and industry standard testing specifications, a series of standardized tests were conducted on the synthesis methods described in Examples 1-3 and Comparative Examples 1-3.

[0057] The yield of the product cyanuric acid was calculated by mass method. First, the mass (m) of the dried cyanuric acid product was weighed using an analytical balance with an accuracy of 0.1 mg. p (g). Theoretical yield (m³) t g) Based on the urea feed mass (m u Based on the molar mass of urea (60.06 g / mol) and the theoretical molar ratio of cyanuric acid to urea for complete conversion (1:3), the following formula was calculated: m t =(m u / 60.06)*(1 / 3)*129.08. Yield (Y, %) is calculated using the formula Y=m p / m t Calculated by multiplying by 100%.

[0058] Product purity was analyzed using a high-performance liquid chromatograph equipped with a UV detector. 10.0 mg of the sample was accurately weighed into a 10 mL volumetric flask, dissolved and diluted to volume with ultrapure water, and filtered through a 0.22 μm aqueous microporous membrane to obtain the test solution. Simultaneously, cyanuric acid standard was accurately weighed to prepare a series of standard solutions of varying concentrations. Chromatographic analysis was performed using an octadecylsilane-bonded silica column, with the column oven temperature set at 30.0 °C. The mobile phase consisted of 0.02 mol / L potassium dihydrogen phosphate buffer and methanol, using a gradient elution program. The total run time was 20.0 min, the flow rate was 1.0 mL / min, the detection wavelength was 210 nm, and the injection volume was 10.0 μL. A standard curve was plotted with the standard solution concentration on the x-axis and the peak area on the y-axis. The linear correlation coefficient should be greater than 0.999, and the purity of the test solution was calculated based on the peak area.

[0059] The recyclability of the catalyst was evaluated through repeated experiments. After each synthesis reaction, the catalyst was washed, dried, and calcined at 300°C for 2.0 h in an argon atmosphere. The catalyst was then used in the next cyanuric acid synthesis experiment with the exact same material ratios and reaction conditions as the first use. The yield of the product obtained in each cycle was recorded to evaluate the catalyst's activity and stability.

[0060] The performance test data above are shown in Table 1.

[0061] Table 1 Performance Test Results

[0062] As can be seen from the above, based on the performance test results, the method of the present invention represented by Examples 1-3 systematically solves several key problems in the existing cyanuric acid synthesis technology compared with Comparative Examples 1-3.

[0063] First, this invention successfully overcomes the core problems of high energy consumption and poor selectivity in traditional high-temperature pyrolysis methods. Comparative Example 1, under catalyst-free conditions, even after reacting at 200℃ for 4 hours, only achieved a yield of 51.1%, with low product purity (87.3%) and a dark yellow color. This directly reflects the low efficiency and numerous side reactions of traditional processes. In contrast, Example 1, at the same temperature and time, significantly increased the yield to 93.2% and achieved a purity of 98.7% by introducing the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modifier prepared according to this invention, with the product being a white crystal. This clearly demonstrates that this modified material, as a heterogeneous catalyst, efficiently catalyzes the directional conversion of urea to cyanuric acid through its abundant acidic sites and nano-confinement effect, achieving near-complete conversion and high selectivity at a relatively mild temperature, fundamentally overcoming the problems of high energy consumption and poor product quality associated with high-temperature methods.

[0064] Secondly, this invention completely avoids the drawbacks of using corrosive solvents and achieves efficient recycling of the catalyst, solving the cost and environmental hazards of solvation processes such as ionic liquid methods. The process of this invention is a pure solid-phase reaction, requiring no liquid solvents, thus eliminating equipment corrosion and wastewater treatment problems at the source. More importantly, the catalyst of this invention exhibits excellent cycle stability. For example, the catalyst in Example 1 maintained a yield of 90.5% after three cycles, with minimal activity loss. In contrast, Comparative Example 2, using only raw montmorillonite, showed significantly lower initial yield (72.2%) and post-cycle yield (63.4%). Comparative Example 3, using unmodified amine material, had a slightly better initial yield (75.6%) and cycle stability (68.9%) than Comparative Example 2, but still far inferior to the examples. This comparison strongly demonstrates the indispensability of the "silanization amine modification" step in this invention: it provides a strong chemical anchoring point for the zirconium active center by firmly grafting amine groups onto the montmorillonite surface, thereby constructing a structurally stable heterostructure with minimal loss of active sites. The material in Comparative Example 3 lacks this stable interface, and the active components are prone to agglomeration or detachment during the reaction and regeneration process, resulting in its catalytic performance and cycle life being unable to match those of the material of this invention.

[0065] In summary, the comprehensive performance of Examples 1-3 clearly demonstrates the overall progress of this invention compared to the prior art: by creating a novel and structurally stable zirconium-based metal-organic framework-montmorillonite heterostructure catalyst, this invention achieves product yields and purity far exceeding those of the uncatalyzed system and the comparative catalytic system while significantly reducing the reaction temperature; its solvent-free, easily separable, and recyclable process design perfectly avoids the corrosion, pollution, and cost problems of traditional methods, providing a truly efficient, economical, and environmentally friendly new route for the synthesis of cyanuric acid that conforms to the principles of green chemistry.

Claims

1. A green synthesis method for cyanuric acid, characterized in that, Includes the following steps: S1. In a mortar, urea and zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material are ground and mixed to obtain a mixture. The mixture is then transferred to a covered quartz boat to obtain a quartz boat containing the material. S2. Place the quartz boat containing the material into the muffle furnace, introduce argon gas, and heat to 180-220℃ to react; S3. After the reaction is complete, allow it to cool naturally to 60-80℃ and remove the reaction product. Transfer the reaction product to a beaker, add deionized water at 78-82℃, and stir. Then filter under reduced pressure to obtain a wet filter cake and filtrate. Wash the wet filter cake with deionized water at 78-82℃ to obtain a washed wet filter cake, filtrate, and washing liquid. S4. The washed wet filter cake is redispersed in hot water at 78-82℃, centrifuged at high speed, and the solid precipitate is collected. The solid precipitate is dried at 78-82℃, and then calcined at 298-302℃ in an argon atmosphere to obtain the regenerated zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material. The filtrate and washing liquid obtained in step S3 are cooled to 0-5℃, allowed to stand, filtered again to obtain crystals. The crystals are washed with deionized water and finally dried in a vacuum drying oven at 78-82℃. The preparation steps of the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material include: A1. By weight, place 8-12 parts of sodium-based montmorillonite in a three-necked flask, add 280-320 parts of deionized water, and stir at 78-82℃ to obtain a suspension; add 35-37 parts of a mixed solution of ethanol and water of 3-aminopropyltriethoxysilane dropwise to the suspension to adjust the pH to 4-5; reflux the reaction at 84-86℃ under nitrogen protection; after the reaction is complete, collect the solid by centrifugation, wash the solid alternately with ethanol and deionized water, and dry it in a vacuum drying oven at 78-82℃ to obtain silanized amino-modified montmorillonite; A2. Disperse silanized amine-modified montmorillonite in 180-200 parts of N,N-dimethylformamide and sonicate to obtain a suspension. Under stirring, dissolve 3.5-4.5 parts of zirconium tetrachloride in 45-50 parts of anhydrous N,N-dimethylformamide and then add it dropwise to the suspension to obtain a mixture. Transfer the mixture to an ice-water bath and continue stirring at 0-5℃. Centrifuge and wash with N,N-dimethylformamide to obtain a zirconium-amine coordination intermediate. A3. Dissolve 1.6-2.0 parts of 2-aminoterephthalic acid in 140-150 parts of N,N-dimethylformamide to obtain solution A; dissolve 2.8-3.2 parts of benzoic acid in 45-48 parts of N,N-dimethylformamide to obtain solution B; redisperse the zirconium-amine coordination intermediate in 92-96 parts of N,N-dimethylformamide to obtain a zirconium-amine coordination intermediate suspension; add the zirconium-amine coordination intermediate suspension to a high-pressure hydrothermal reactor; add solution A to the high-pressure hydrothermal reactor, then add solution B; place the high-pressure hydrothermal reactor in a 115-125℃ forced-air drying oven to react and obtain the reaction product; A4. Cool the reaction product to room temperature, centrifuge to collect the precipitate, wash the precipitate sequentially with N,N-dimethylformamide and anhydrous methanol to obtain the washed precipitate, soak the washed precipitate in methanol to obtain the wet material; dry the wet material at 78-82℃ to obtain the powder, place the powder in a tube furnace and perform heat treatment under argon protection.

2. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step S1, the mass ratio of urea to the zirconium-based metal-organic framework-montmorillonite heterostructure inorganic modified material is (4.8-5.2):(0.4-0.6).

3. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step S2, the reaction time is 3-5 hours after heating to 180-220℃.

4. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step S3, the stirring time is 20-40 minutes.

5. The green synthesis method for cyanuric acid according to claim 1, characterized in that, In step S4, the subsequent calcination at 298-302℃ in an argon atmosphere takes 2-4 hours.

6. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step A1, the reflux reaction at 84-86℃ takes 24-30 hours.

7. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step A2, stirring is continued at 0-5℃ for 6-8 hours.

8. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step A3, the reaction time in a forced-air drying oven at 115-125℃ is 72-80 hours.

9. The green synthesis method of cyanuric acid according to claim 1, characterized in that, In step A4, the heat treatment process involves heating to 245-255℃ and holding at that temperature; then further heating to 295-305℃ and holding at that temperature.

Citation Information

Patent Citations

  • Preparation method of high-yield cyanuric acid and its derivatives sodium dichloroisocyanurate and trichloroisocyanuric acid

    CN102516188A

  • Energy-absorbing method based on hybrid cross-linked network dynamic polymer

    CN108342037A